Kepentingan Nasional Tiongkok Dalam Investasi Pengembangan Electric Vehicle di Indonesia Periode 2014-2023 - Kanzi Pratama Artananda Naufal; Ica Wulansari (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
In the past decade, China has emerged as a global economic power with significant geopolitical influence, reshaping the international power distribution. As the world’s second-largest economy and leading exporter, China’s role in global trade and foreign direct investment is crucial. However, this economic growth comes with considerable environmental challenges, notably high greenhouse gas (GHG) emissions that make China one of the world's top emitters. To address these challenges, China has implemented a range of low-carbon economic policies, including climate resilience targets and a shift toward renewable energy. One of China’s primary strategies for achieving its low-carbon goals is the electrification of the transportation sector, with a focus on electric vehicle (EV) development. This policy aims not only to reduce air pollution and dependence on fossil fuels but also to boost the green technology industry. However, the electrification efforts create a high demand for essential resources, such as nickel, a key component in EV batteries. Indonesia, as one of the world’s largest nickel producers, has become a strategic partner for China in meeting these resource demands. Through substantial investments in the mining and nickel processing industries, China has strengthened its economic ties with Indonesia while supporting the growth of Indonesia’s EV infrastructure. China’s Belt and Road Initiative (BRI) also plays a crucial role in enhancing infrastructure connectivity and investment in Southeast Asia, particularly in Indonesia, which has been one of the major recipients of BRI investments.